Eating with our eyes (closed): Effects of visually associating animals with meat on antivegan/vegetarian attitudes and meat consumption willingness. (September 2019) - Earle, Megan; Hodson, Gordon; Dhont, Kristof; MacInnis, Cara
Negative attitudes toward vegetarians/vegans (i.e., veg*ns) are common, particularly among those who desire/like/consume meat more. In two studies, we replicated and extended past work, showing that visual reminders of meat's animal origins (vs. images of meat alone) decreased meat consumption willingness via increased empathy for animals, distress about meat consumption, and disgust for meat. We also assessed how animal–meat reminders influence antiveg*n attitudes. In Study 1 ( N = 299) experimental animal–meat reminders (vs. meat-alone images) indirectly reduced negative attitudes toward veg*ns via increased empathy and distress (together, but not independently). The same manipulation in Study 2 ( N = 280) lowered antiveg*n attitudes through greater empathy and lowered veg*n threat through greater distress. Implications for promoting less antiveg*n attitudes are discussed.